A novel hyaluronic acid-based dissolving microneedle patch loaded with ginsenoside Rg3 liposome for effectively alleviate psoriasis. (December 2022) - Huang, Chi; Gou, Kaijun; Yue, Xuan; Zhao, Shiyi; Zeng, Rui; Qu, Yan; Zhang, Chen
Graphical abstract: Highlights: Dissolving microneedles are promising devices used for painless transdermal drug delivery. Ginsenoside Rg3 engineered liposomes are easily manufactured, stable, and provide a novel potential platform for psoriasis. Liposome-in-microneedles strategy can provide site-specific drug delivery, increase drug accumulation in the epidermis. Abstract: Psoriasis is a chronic scaly skin disease, which is associated with abnormal immune system function, inflammatory cell infiltration. The disadvantages of traditional treatment of psoriasis are poor efficacy, recurrence of the condition, long treatment time, and systemic side effects due to a lack of an appropriate drug delivery system. A liposome-in-Microneedles (MNs) based transdermal drug delivery system had been developed to provide efficient site-specific drug delivery, stable drug release and enhanced permeability. Firstly, liposomes were loaded with Ginsenoside Rg3 (a small molecular compound with anti-inflammatory and immune regulation functions), then Rg3-liposomes (Rg3-Lipo) were successfully loaded into MNs. Rg3-Liposome-MNs (Rg3-MNs) with the mechanical property of 0.59 N/needle, could easily penetrate the epidermis and release Rg3-lipo to regulate the immune response. The efficacy of Rg3-MNs was evaluated by IMQ-induced psoriasis-like dermatitis in mice. Rg3-MNs significantly (p < 0.01) decreased the epidermal thickness, dermal papillary edema, and the possible mechanism was to markedly reduce (p < 0.01) the levels of IL-17, IL-23, and TNF-α. In addition, we found that Rg3-MNs might improve psoriasis by inhibiting the activation of the STAT3/p-STAT3 signaling pathway. In brief, this study provides an ideal loaded anti-inflammatory and immunoregulatory drug delivery system to treat psoriasis.